Promoting students’ environmental literacy through PBIB learning model - P. Prasetiyo; Mimien Henie Irawati Al Muhdhar; I. Ibrohim; Murni Saptasari (University of Muhammadiyah Malang, 2024)
Low literacy levels are believed to be one of the causes of environmental damage problems. It is felt that the current implementation of the problem-based learning model is still not optimal in increasing students' environmental literacy, especially regarding sustainable issues. This research aims to (1) produce a sustainable issue-based learning model, and (2) test the level of validity and reliability of the model. The research was carried out at Malang State University and PGRI University Semarang involving biology learning experts, educational technology experts, and environmental experts as research subjects. The instrument in this research is an expert validation sheet. Validation results were analyzed using the average score while reliability was analyzed using percentage agreement. The research results show that the development of PBIB syntax including orientation, concept strengthening, observation, investigation, report, and reflection is classified as valid with a score of 3.87, while the reliability is 3.88 (reliable). This research indicates that the PBIB model can be used in learning and potentially increase students' environmental literacy.